A CO Survey of the Entire Northern Sky - Dame, T. M.; Thaddeus, P. (The Astrophysical journal. Supplement series, 2022)
We present a very large extension of the Galactic plane CO survey of Dame et al. to the entire northern sky ( δ > −17°). The extension was carried out with the same telescope as was used for the plane survey, the CfA 1.2 m, and perfectly meshes with its irregular boundaries in latitude. A total of 382,202 CO(1–0) spectra uniformly sample the high-latitude sky with a true-angle spacing of 0.°25 or better. The final reduced and folded spectra have a uniform sensitivity of 0.18 K in 0.65 km s −1 channels and provide a velocity coverage of ±47.1 km s −1 . We describe the observational techniques and the data reduction and provide various summary maps of the spatial and velocity distributions of CO emission over the northern sky, and a catalog of the molecular clouds we found there. We also describe the CO spectral line data cubes that we have made available online.